Moral disengagement as mediator and guilt as moderator between cyber moral literacy and cyberbullying among late adolescents - Ya-Xing Sun; Cui-Hong Cao; Zhi-Jun Tang; Fei-Mei Huang; Xiao-Bin Zhong; I-Hua Chen (Scientific Reports)
Abstract The rapid growth of internet usage has led to increased cyberbullying among adolescents, with varying rates reported across countries. This study aimed to investigate the impact of cyber moral literacy on cyberbullying among late adolescents, examining both the mediating role of moral disengagement and the moderating effect of guilt on the relationship between cyber moral literacy and cyberbullying. Data were collected from 7837 late adolescent students (aged 18–21 years) at four universities in Sichuan Province, China. Scales measuring cyber moral literacy, cyberbullying, moral disengagement, and guilt were employed. Structural Equation Modeling was used to test hypothesized relationships. Cyber moral literacy showed a strong negative association with cyberbullying. The relationship between cyber moral literacy and cyberbullying was partially mediated by moral disengagement. Additionally, guilt moderated the direct relationship between cyber moral literacy and cyberbullying, with this negative relationship being stronger among individuals with high guilt compared to those with low guilt. The study highlights the complex interplay of moral, cognitive, and emotional factors in adolescent online behavior. The findings suggest that enhancing cyber moral literacy could be particularly effective in reducing cyberbullying, especially among individuals who experience higher levels of guilt. Additionally, addressing moral disengagement mechanisms could help strengthen the preventive effect of cyber moral literacy on cyberbullying. These insights contribute to our understanding of creating a more harmonious online environment for late adolescents.